Operações de serviços de pós-venda baseadas em conhecimento: o caso Carrier Transicold Brasil - Viegas, Nereu Batista (Universidade do Vale do Rio dos Sinos, 2010)
The performance of technical assistance depends on how information and knowledge are disseminated to a network of services. This work was developed with the aim of identifying how the operations of after-sales service can generate competitive categories for a technical assistance network based on quality management and knowledge. This case study included participant observation by the researcher, and research on the perception of managers of the manufacturing company and subcontractors. A sample of 8 companies, total 85, which provide technical support service to a multinational company, which manufactures bus air conditioned and equipment for refrigerated trucks, was investigated in order to identify the main factors capable of delivering reliable, quality service, with information, resources and support available from the organizational knowledge. Among the results of this study, it can be noted that the quality and reliability of products are essential for the survival of a network of services. Technical assistance will be competitive if the manufacturer maintains continuing concern, offering quality products, application and dissemination of correct information. And, for the customer to have credibility in the servicing, this should have their technicians trained at regular intervals. This brings agility to solve problems of equipment and therefore greater productivity for the service provider. The importance of after-sales service to manufacturers of products is vital for maintaining and growing in the market. Upon failure of equipment, this must be repaired as quickly as possible and safely, avoiding problems that might interfere with the decision of the client for the next purchase.
Keywords: Operações de serviços; Qualidade em serviços; Gerenciamento do conhecimento; Serviços de pós-venda; Service operations; Service quality; Knowledge management; After sale service; ACCNPQ::Ciências Sociais Aplicadas::Administração